FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KOPI ARABIKA KE ASIA - Trirahayuni Trirahayuni; Khairil Anwar; Cut Putri Mellita Sari; Umaruddin Usman (Jurnal Ekonomi Pertanian Unimal, 2023)
This study analyzed the factors influencing Arabica coffee exports to Asia. This study used secondary data in the form of panel data analysis, which was a combination of time series and cross-section, the time series data used were 2005-2020 and the cross-section data used were five Arabica coffee export destinations to Asia. The panel data analysis method was used to analyze the price of Arabica coffee in Asian countries and the per capita income of Asian countries. The results indicated that the factors that significantly influenced the export of Arabica coffee to Asia included income per capita in Asian countries, but only the price of Arabica coffee in Asian countries had a positive and insignificant effect on Arabica coffee exports to Asia.